PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI DI PDAM TIRTA MOEDAL KOTA SEMARANG - Adhim, Muhamad Fauzul; Mustam, Moch.; Dwimawanti, Ida Hayu (Journal of Public Policy and Management Review, 2016)
Water is a source of life for human beings and having an important role for the continuity of human life. PDAM as company that propose the availability of water in indonesia certainly must have optimal performance in fulfilling the needs of the people. Employees have certainly a major role in good or poor performance PDAM because it is the essential element in organization. One of the factors that influences the performance employees is competence human resources and climate organization. If competence human resources and climate organization good, so the employee performance will also high, so instead. The purpose of this study is to find the influence of competence human resources and climate organization on performance employees in PDAM Tirta Moedal Semarang City with the methodology used is research quantitative. The data obtained in this research through koesioner. An analysis of the data used was a correlation coefficient kendall and coefficients concordance kendall. Data processing using spss 16.0 program. Based on the calculation on in data analysis, be known that hypothesis in this research could be accepted because competence human resources and climate organization impact on the employee performance.